2021
DOI: 10.1021/acscatal.0c05671
|View full text |Cite
|
Sign up to set email alerts
|

How Strain Alters CO2 Electroreduction on Model Cu(001) Surfaces

Abstract: Carbon dioxide electrolysis powered by renewable energy is a potentially attractive approach to close the carbon cycle and produce key chemical feedstocks. Here, we demonstrate the substantial influence of tensile strain on the selectivity of CO2 reduction toward higher value-added, multicarbon products by modulating the residual mismatch strain of Cu(001) thin film catalysts grown epitaxially on single-crystal Si substrates. By decreasing film thickness from 100 to 20 nm, up to 0.22% tensile strain is introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 65 publications
1
25
2
Order By: Relevance
“…Although the promoting effect of tensile strain on C-C coupling and suppression on the competing HER have been demonstrated theoretically, [51][52] a controversy exists in the literature on how the tensile strain in Cu affects the C 1 products during the CO 2 RR. For instance, a recent study reported that tensile strain in Cu is unfavorable for the formation of C 1 products, 22 which is inconsistent with our observations and the conclusions of other studies. 24,52 Another study concluded that tensile strain has different effects on the production of CH 4 , depending on the thickness of the Cu layer.…”
Section: Strain Effectscontrasting
confidence: 99%
See 3 more Smart Citations
“…Although the promoting effect of tensile strain on C-C coupling and suppression on the competing HER have been demonstrated theoretically, [51][52] a controversy exists in the literature on how the tensile strain in Cu affects the C 1 products during the CO 2 RR. For instance, a recent study reported that tensile strain in Cu is unfavorable for the formation of C 1 products, 22 which is inconsistent with our observations and the conclusions of other studies. 24,52 Another study concluded that tensile strain has different effects on the production of CH 4 , depending on the thickness of the Cu layer.…”
Section: Strain Effectscontrasting
confidence: 99%
“…Density functional theory (DFT) calculations suggest that, according to the d-band theory, lattice strain can trigger a shift of the d-band center of the metal and tailor its catalytic activity. 19,[22][23]47 Taking Cu derived from Cu 2 (OH) 2 CO 3 as an example, four slab models were built, including strain-free Cu(111) and Cu(100), Cu(111) with 0.55% tensile strain (denoted as Cu(111)-strain), and Cu(100) with 0.72% tensile strain (denoted as Cu(100)-strain). By analyzing their projected density of states (PDOS) of d-band, the (111) and (100) surfaces with tensile strain have higher d-band centers than their strain-free counterparts (-1.999 vs. -2.021 eV, and -2.120 vs. -2.158 eV, respectively; Figs.…”
Section: Strain Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the many optimization strategies, bimetallic structures and strain engineering have recently emerged as effective strategies to enhance catalytic performance by altering the electronic structures of catalysts. [7][8][9][10] Bimetallic nanoparticles often create strains due to lattice mismatch between the two components. 11 Nørskov et al proposed that strain can change the overlapping of orbitals in transition metal atoms and thus change the width of their d-band.…”
Section: Introductionmentioning
confidence: 99%